Determining the Behaviour of Wild Plants’ Use in Meru, Kenya - Ibui, Alfreda Kajira (Highlights on Medicine and Medical Science Vol. 3, 2021)
The ethnobotanical record resulting from interactions between the Meru people and their wild plants shows a high reliance on medicinal and non-medicinal uses of these plants. In this part of Africa, wild plants are increasingly being used for medicine, food, material, social purposes, construction, fuel, environmental beauty, and wind and dust breaks. In the fight against diseases and ailments, medicine made from wild plants is beginning to compete with conventional medicines. The availability of numerous plant species growing in the area, with which humans have interacted for centuries, highlights the dependence. Indeed, the favourable climate for equatorial forests, where temperatures favour the development of numerous plant species, contributes to this region's status as a pharmacy in the making. A total of 567 plant specimens collected from three districts of the greater Meru area have been reported to be used to cure a variety of diseases as well as to meet other non-medicinal needs such as fruit, fuel, and materials. Data collected through structured interviews from respondents in the region reveal significant factors that play major roles in the lives of the people thus influencing their social and cultural behaviour. It is concluded that the use of medicinal plants in Meru as a complement to primary health care is observed and recorded among the people. The great knowledge of the people relating to useful plants and their medical properties was reported to stretch back in time to several generations.